1990
DOI: 10.1111/j.1600-0447.1990.tb01404.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism among Taiwan aborigines defined by the Chinese Diagnostic Interview Schedule: a comparison with alcoholism among Chinese

Abstract: The prevalence of alcoholism was reported to be 0.1% in an aboriginal study on Taiwan using the census survey method in the 1950s. This study adopted a modified Chinese Diagnostic Interview Schedule to determine the prevalence of DSM-III-defined alcohol abuse (AA) and alcohol dependence (AD) in the Atayal, Paiwan and Yami ethnic groups of Taiwan aborigines. Stratified random sampling was used. The sample sizes of Atayal, Paiwan and Yami were 793, 656 and 106 respectively. The prevalence rates of DSM-III-define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Later in the 1980s, Hwu et al reported a 100-fold increase in prevalence (of 1.5% AD in the Taiwanese community, and 10% in Aboriginal tribes). 4,8 The findings of the drastic increase in AD prevalence, caused academic debate concerning the issue of methodology, like interviewers' reliability and Chinese version's validity. A further hospital-based survey by psychiatrists, showed that the prevalence of AD was 6.6%, 5 times higher among inpatient s than community samples.…”
Section: Epidemiology Of Ad In Taiwanmentioning
confidence: 99%
See 2 more Smart Citations
“…Later in the 1980s, Hwu et al reported a 100-fold increase in prevalence (of 1.5% AD in the Taiwanese community, and 10% in Aboriginal tribes). 4,8 The findings of the drastic increase in AD prevalence, caused academic debate concerning the issue of methodology, like interviewers' reliability and Chinese version's validity. A further hospital-based survey by psychiatrists, showed that the prevalence of AD was 6.6%, 5 times higher among inpatient s than community samples.…”
Section: Epidemiology Of Ad In Taiwanmentioning
confidence: 99%
“…For example, the prevalence of alcohol dependence among aboriginal people in Taiwan is 10 folds higher than that of Han people. 3,4 Taiwanese people, with a low prevalence of AD, have long been thought to be the ethnicity immune to AD. 4 However evidence revealed that the alcohol problem is severe in Taiwan.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we recruited only males for three reasons: (a) antisocial personality disorder exists mostly in males [Lu et al, 2002[Lu et al, , 2003]; (b) alcoholism occurs about 10 times more frequent in males than in females among the Han Chinese population in Taiwan [Helzer et al, 1990;Hwu et al, 1990]; (c) the drinking pattern usually differs between male and female alcoholics [Zucker, 1986].…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…It is of value to provide this kind of data from different ethnic groups of different cultural backgrounds. Epidemio logical studies in Taiwan Chinese [6,7] and aboriginal people [8] showed that the diagnos tic subtypes of alcohol abuse and dependence defined by the criteria of diagnostic and sta-tistical manual, 3rd edition (DSM-III) [9] probably represented different disease enti ties because of different risk factors and the probable different etiological models pro posed [10,11], After these serial studies, de tailed descriptive study of community cases of alcohol abuse and dependence is needed to explore the evolving process of alcoholism. Such data will enrich clinical understanding of alcoholism in community and provide a way toward subtyping alcoholism based on the psychopathological process.…”
Section: Introductionmentioning
confidence: 99%